2009
DOI: 10.1097/meg.0b013e3283081afe
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated infliximab infusions are safe and well tolerated in patients with inflammatory bowel disease

Abstract: Rapid infusion of infliximab is safe and well tolerated, with no increase in infusion-related reactions. Where reactions do occur, they are usually mild, allowing completion of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…The observation that in infliximab, naïve patients and after six 2‐h infusions switch to a 1‐h infliximab maintenance infusion had a similar infusion reaction rate as a 2‐h infliximab maintenance infusion is consistent with the current literatures 18, 19 . One limitation with our study is the risk of selection bias, because not all eligible patients entered the 1‐h infusion protocol.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The observation that in infliximab, naïve patients and after six 2‐h infusions switch to a 1‐h infliximab maintenance infusion had a similar infusion reaction rate as a 2‐h infliximab maintenance infusion is consistent with the current literatures 18, 19 . One limitation with our study is the risk of selection bias, because not all eligible patients entered the 1‐h infusion protocol.…”
Section: Discussionsupporting
confidence: 81%
“…These results demonstrate that a 1‐h infliximab infusion protocol during maintenance therapy is safe and well tolerated. Previous studies have included much smaller numbers of patients and fewer numbers of infusions 16–22 . Indeed the current study has over double the number of total infusions relative to the next largest study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent metaanalysis found the presence of these antibodies associated with a higher risk of acute, but not delayed infusion reactions [18]. The concomitant use of immunomodulators has consequently been recommended to contain the rate of these reactions [19,20], but current data on their efficacy are conflicting [10,13,16,21]. Our multivariate analysis indicated that the concomitant use of immunomodulators is not a protective factor, though only a small proportion of the patients in our sample were taking these drugs.…”
Section: Discussionmentioning
confidence: 60%
“…incomplete data and different definitions for infusions reactions), it confirms that rapid IFX infusions in selected patients are not associated with an increased risk of adverse events. [2][3][4][5][6] This strategy could save costs and have a substantial impact on healthcare resources and absenteeism from work or school. sions (Phase-M) proceeded to phases 2 and 3.…”
mentioning
confidence: 99%